2018
DOI: 10.18240/ijo.2018.03.18
|View full text |Cite
|
Sign up to set email alerts
|

Three-year results of small incision lenticule extraction and wavefront-guided femtosecond laser-assisted laser in situ keratomileusis for correction of high myopia and myopic astigmatism

Abstract: Both SMILE and wavefront-guided FS-LASIK procedures provide good visual outcomes. Both procedures are effective and safe, but SMILE surgery achieve more stable long-term refractive outcome and better control of early postoperative dry eye as compared to FS-LASIK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 34 publications
4
22
0
Order By: Relevance
“…We found a trend of regression in our study with achieved SE of −0.26 D, −0.33 D, and 0.43 D at 1, 3, and 5 years, respectively. In line with Xia et al [ 19 ], the difference was not significant at 3 years. However, we found that the regression between 1 and 5 years was statistically significant.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found a trend of regression in our study with achieved SE of −0.26 D, −0.33 D, and 0.43 D at 1, 3, and 5 years, respectively. In line with Xia et al [ 19 ], the difference was not significant at 3 years. However, we found that the regression between 1 and 5 years was statistically significant.…”
Section: Discussionsupporting
confidence: 90%
“…To the best of our knowledge, there is no study reporting 5-year results after SMILE in cases of high myopia. Xia et al [ 19 ] compared 3-year results between SMILE and LASIK. Although they reported a statistically significant regression in the LASIK group, the mean regression in the SMILE group between 1 year and 3-years visits was only 0.14 D, and it was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are limited data on the comparative efficacy between procedures with respect to myopia severity. A few studies have investigated SMILE efficacy in patients with high myopia (6.0D myopia or more), which have shown good visual outcomes and safety profiles in treated eyes [1618]. However, one prospective study including 165 eyes of 86 patients in China reported a trend towards undercorrection by SMILE in eyes with myopia greater than 6.0 D [17].…”
Section: Resultsmentioning
confidence: 99%
“…57 The benefits of SMILE over LASIK for patients with high refractive error have not been conclusively established. 64 However, it is possible that the higher laser energy required for LASIK in high myopes results in more inflammation, poorer healing, and hence greater postoperative aberrations. In contrast, the amount of laser energy required in SMILE is comparatively low even when high refractive errors are being corrected.…”
Section: Other Patient-reported Outcome Measuresmentioning
confidence: 99%